Anatomical investigations of Piper amalago (jaborandi-manso) for the quality control - Santos,Vera L.P. dos (2015)
Abstract Piper amalago L., Piperaceae, popularly known as jaborandi-manso, is a shrub that spans a height of 2–7 m. It can be found in the regions of Southern America downward up to the south of Brazil. Traditionally it is used to treat digestive problems, heart problems, and burns. This study aims to conduct an anatomical investigation and analysis of the leaves and stems of P. amalago through electron scanning and optical micro techniques. The analysis showed that P. amalago has a hypostomatic leaf, with a subepidermal layer on its surface. There are grandular trichomes that resemble sacs, conic non-glandular trichomes, dorsiventral mesophyll, and a plano-convex midrib having a single vascular bundle in the center. The petiole is short with irregularly shaped and adaxially grooved. The stem is circular in shape and contains two circles of vascular bundles and a sclerenchymatic sheath in the perimedular region. These anatomical features of the Piper amalago's leaves and stems make it easy to pick it out among other species of the Piper genus. This is helpful when conducting quality control process.